Inequality, Lobbying, and Resource Allocation - Esteban, Joan; Ray, Debraj (American Economic Review, 2006)
This paper describes how wealth inequality may distort public resource allocation. A government seeks to allocate limited resources to productive sectors, but sectoral productivity is privately known by agents with vested interests in those sectors. They lobby the government for preferential treatment. The government—even if it honestly seeks to maximize economic efficiency—may be confounded by the possibility that both high wealth and true economic desirability create loud lobbies. Broadly speaking, both poorer economies and unequal economies display greater public misallocation. The paper warns against the conventional wisdom that this is so because such governments are more “corrupt.”